The Use of Geoinformation Systems in the Study of the Land Fund of Household and Dekhkan Farms - Abdukadirova Muharram Arabboevna; Yokubov Sherzodbek Shavkat o‘g‘li (Zien Journals, 2022)
The article presents an overview of the geoinformation system that will help the student to better understand modern works on territorial planning, land management, cadastre, and assessment of the state of the natural environment.
Keywords: Geoinformation; GIS; cadastre; land formation